Going private: Are private prisons cost‐saving options for states?. (29th June 2020) - White, Weston; Pena, Anita Alves; Weiler, Stephan
Abstract: As prison populations have increased, states have often turned to private prisons in an effort to save on correctional costs. This paper first considers the trade‐offs between private and public prisons, then assesses the cost‐effectiveness of such strategies across all 50 states over 1999–2015 using a fixed‐effects panel model. We find that private prisons provide no significant systematic cost savings over the period of study, adding econometric clarification to previously inconclusive case study evidence.